The future of agriculture and food: Evaluating the holistic costs and benefits. (December 2019) - Sandhu, Harpinder; Müller, Alexander; Sukhdev, Pavan; Merrigan, Kathleen; Tenkouano, Abdou; Kumar, Pushpam; Hussain, Salman; Zhang, Wei; Pengue, Walter; Gemmill-Herren, Barbara; Hamm, Michael W; Tirado von der Pahlen, Maria Cristina; et al.
Inadequacies of the current agriculture and food systems are recognised globally in the form of damages to environment and human health. In addition, the prevailing economic and policy systems do not reflect these damages in its accounting systems and standards. These shortcomings lead to perverse and pervasive outcomes for society at large. Our proposal is to consider all social and environmental externalities – both negative and positive, in global agriculture and food systems and reflect them in an economic system by evaluating comprehensive costs and benefits. This can be done by adopting an innovative, universal, and inclusive framework (the 'TEEBAgriFood' framework) in order to stimulate appropriate policy responses.